2020
DOI: 10.1016/j.ydbio.2020.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Context-specific functions of Notch in Drosophila blood cell progenitors

Abstract: Notch signaling regulates differently distinct populations of blood cell progenitors of the Drosophila larval hematopoietic organ..

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 50 publications
2
36
0
Order By: Relevance
“…It is well established that Notch signaling plays a pivotal role in cellular communication, regulating stem cell maintenance, proliferation, and differentiation during embryonic development, as well as tissue homeostasis and stem cell self-renewal in multiple adult organ systems [ 55 , 56 , 57 ]. The role of Notch in controlling stem cell population and differentiation decisions is considered to be cell context specific [ 55 , 58 , 59 ]. There have been some conflicting reports regarding the regulatory role of Notch signaling in the corneal epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that Notch signaling plays a pivotal role in cellular communication, regulating stem cell maintenance, proliferation, and differentiation during embryonic development, as well as tissue homeostasis and stem cell self-renewal in multiple adult organ systems [ 55 , 56 , 57 ]. The role of Notch in controlling stem cell population and differentiation decisions is considered to be cell context specific [ 55 , 58 , 59 ]. There have been some conflicting reports regarding the regulatory role of Notch signaling in the corneal epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, different subpopulations of Dome+ progenitors in the MZ were precisely defined with distinct markers. The most central progenitors that express Tep4 or collier ( col , also known as knot ) are defined as the Core progenitors [ 35 ], and the neighboring progenitors that lack Tep4 or col expression are named Distal progenitors [ 36 ].…”
Section: Drosophila Lymph Glandmentioning
confidence: 99%
“…However, the requirement of PSC cells as well as the role of col in the PSC for progenitor maintenance have been challenged by recent studies [ 35 , 43 ], in which the genetic ablation of the PSC did not cause a loss of prohemocyte population. Later, additional studies repeatedly demonstrated that the signaling molecules sent out from the PSC, such as Hh and Ser, are indeed required to restrain hemocyte differentiation and maintain the MZ progenitors in an undifferentiated state [ 35 , 36 , 44 ], further supporting the critical role of the PSC as a hematopoietic niche. However, the role of col in the PSC has to be reconsidered.…”
Section: Drosophila Lymph Glandmentioning
confidence: 99%
See 2 more Smart Citations